Kampong Putu / Muhammad Amirul Azlan ... [et al.] - Azlan, Muhammad Amirul; Mazlan, Farah Fatin; Johari, Muhammad Sabri; Abd Ghani, Mohd Afizal; Rosly, Khairul Akmal (2009)
KAMPONG PUTU is a one of the types of food stall establishment that aims to provide the best method of business which uses certain technological approach to delight and attract customers, and at the same time to be the first entrepreneur which selling these three types of putu at the next level, which were not just only sell ‘putu mayam’, ‘putu piring’ and also ‘putu buluh’ in small size of market such as at night market or weekly market. The main selling points for ‘KAMPONG PUTU’ would be the operation of our business. We started our business at 7am which is the breakfast hour for all people. Early in the morning, we will prepare before our stall open with all preparation same with every business in Malaysia but the difference between our company and others is we were focused especially in terms of time management. This is important because by professional at time management will attract people to go to our stall anytime because they can get the best product of ours even if they were in hurry or urgent. With a minimum of 2 minutes to serves each customer will make sure no more waiting time for our customer to get the fresh and tasty putu. We had chosen three types of putu as our product. The idea to make these three putu’s comes after doing observation and small research on why people only sell these three putu’s at night market or weekly market which customers can only buy these foods once or twice per week. Our Business Plan is pointing to become first official producer and supplier of ‘putu mayam’, ‘putu piring’, and ‘putu buluh’. Our target costumers are around The Spring Shopping Mall and also who comes to our stall.